The Legality of Courts Established by Armed Groups in the Context of NIAC with an Emphasis on the Stockholm District Court Judgment - Iman Montazeri; Mohammad Hossein Ramezani Ghavam Abadi (Faṣlnāmah-i Pizhūhish-i Huqūq-i ̒Umūmī, 2021)
One of the significant features of NIAC (non-international armed conflict) is the establishment of a court by armed groups. Though states consider the establishment of a court as a sovereign privilege that belongs only to the states, armed groups consider the establishment of a court as a means to maintain the law and order among its members and to create order and security in the area under their control. International community considers the establishment of a court by armed groups as an alternative for summary execution. While it seems that humanitarian law that apply to internal conflict gives the permission to armed groups to prosecute its own members and civilians, the legal basis for the establishment of the courts by armed groups in these conflicts is ambiguous. Regardless of the vagueness of the legal basis for establishing a court by armed groups in armed conflicts, the main criticism brought to these courts is that these courts do not have the ability to provide fair trial guarantees in their trials. In this paper, we are examining the legal basis for the establishment of a court by armed groups, the fair trial guarantees  and the most recent judicial precedent in this regard.